Characterization of the techno-functional properties of starch from Purple yam (Dioscorea alata), Hawthorn yam (Dioscorea rotundata) and Diamante 22-type yam • (2018)
This study is aimed at evaluating the techno-functional properties of starches from several yam species (Purple yam, Hawthorn yam and Diamante 22-type yam). Analytical procedures were performed according to the methods described by different authors in order to calculate waterabsorption index (WAI), water-solubility index (WSI), swelling power (SP) and syneresis. Likewise, descriptive statistics and experimental designs for interpretation of the results were also performed. The results showed that Hawthorn yam has the highest WAI (15.15 g gel/g sample, at 90°C). While WSI was similar for all species, SP is dependent on the temperature with values of 16.10 g gel/g sample (Purple yam and Hawthorn yam), and 11.25 g gel/g sample at 90°C (Diamante 22-type yam). All yam species underwent progressive reduction in syneresis, which suggests that these types of starches could be used to manufacture foods that require maintaining moisture levels.